Elasticity Analysis of Production Cost Against Income of Broiler Business with Open-House and Closed-House System in Banyumas Regency - Sri Mastuti; Nunung Noor Hidayat; Rahayu Widiyanti; Endro Yuwono; Danang Nur Cahyo; Krismiwati Muatip; Novie Andri Setianto; Mochamad Sugiarto; Lis Safitri; Alief Einstein; Oentoeng Edy Djatmiko; Benny Satria Febrianto (ANIMAL PRODUCTION, 2023)
In this study, the elasticity of production costs to broiler business income with the partnership pattern in Banyumas regency and production costs and broiler business income with open and closed house systems were examined. The survey approach was used to conduct the research. As the research site, Banyumas regency, one of the hubs for broiler farming in Central Java, was deliberately chosen. Commercial broiler farmers were categorized according to their housing system when choosing the respondents, and 31 farmers used the open housing system, whereas 30 farmers used the closed housing system. The elasticity of production costs to revenue was examined using multiple linear regression while production costs and profits were assessed financially. According to the findings, commercial broiler farmers made an average of IDR 3,626,578 and IDR 4,896,844 each month for 1000 birds in open and closed houses, respectively. The price of DOC, the depreciation of housing, and the depreciation of the farmers' equipment all have a big impact on their revenue. This study's conclusion is that by lowering broiler mortality and making the best use of housing and equipment, farmers may increase their profitability.